Nasal airway epithelial repair after very preterm birth. Issue 2 (7th June 2021) - Hillas, Jessica; Evans, Denby J.; Ang, Sherlynn; Iosifidis, Thomas; Garratt, Luke W.; Hemy, Naomi; Kicic-Starcevich, Elizabeth; Simpson, Shannon J.; Kicic, Anthony
Preterm birth rates are increasing and now account for >11% of global births. Simultaneously, advances in neonatal care have led to increased survival of lower gestation neonates. A complication of preterm birth, and the biggest determinant of survival, is lung and airway immaturity. After preterm birth, the immature respiratory system is exposed to pro-inflammatory stimuli like injury from resuscitation and oxygen toxicity. The airway epithelium, the physical barrier between insults and the airways, is particularly vulnerable to injury. If epithelial barrier integrity cannot be restored rapidly following damage ( i.e. via aberrant repair), the respiratory system is left unprotected, increasing the risk of infection, inflammation and tissue damage. Altered epithelial repair may play an important role in the ongoing respiratory health problems experienced by preterm survivors, including severe respiratory infections throughout early life, or low and declining lung function [1–3]. Deficits are further exacerbated in those with bronchopulmonary dysplasia (BPD). The mechanisms contributing to ongoing respiratory problems are currently unknown, although probably begin in early life. Until now, understanding the role of the preterm epithelial barrier has been limited by a lack of appropriate cellular models. Our study aimed to assess the reparative capacity of the airway epithelium in survivors of preterm birth and its association with early life outcomes, with the hypothesis that preterm airway epithelial cells have an abnormal repair mechanism. Nasal epithelial cells from very preterm infants have a functional defect in their ability to repair beyond the first year of life, and failed repair may be associated with antenatal steroid exposure https://bit.ly/39OFJs7